Evaluation of blind sensing techniques in multiple wireless microphones environments - Dionísio, Rogério Pais (2013)
This work focuses on the evaluation of blind sensing techniques for the detection of multiple wireless microphones in the UHF band, by means of simulation. The metrics used for the comparisons include probability of detection, probability of false alarm and minimum SNR detected for a given observation time. As an example, simulation results showed that blind detection algorithms can sense multiple wireless microphone signals with SNR = -19 dB, in a Rayleigh channel environment, considering 100 ms sensing time, 90 % probability of detection and 10 % probability of false alarm. In these conditions, blind detection techniques suffer maximum SNR degradation of 3.5 dB, as compared with single wireless microphone scenarios.